The Influence of Financial Literacy, Financial Technology and Financial Self-Efficacy on Financial Inclusion - Pamungkas, Wihandaru Sotya; Setyani, Sherly Rehula (Journal of Economics, Assets, and Evaluation, 2024)
This research aims to find empirical evidence of the influence of financial literacy (FLT), financial technology (FTC), and financial self-efficacy (FSE) on financial inclusion (FIC). This research is based on inconsistent previous research findings. This research uses a sample of students still actively studying at Universitas Muhammadiyah Yogyakarta (UMY). The sampling method uses purposive and convenience sampling, namely active students from the 2019-2022 class and easy to find. Data was obtained by distributing questionnaires using Google Forms from 180 respondents. The analysis tool uses structural equation modeling (SEM). The analysis results found that FLT, FTC, and FIC had a positive effect on FSE. This finding implies that individuals and society can access financial products and services because they know the availability of technology and the belief that using financial products and services has benefits.